1996
DOI: 10.1111/j.1527-2001.1996.tb01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Double Binds: Latin American Women's Prison Memories

Abstract: Scant attention given to gender in Latin American prison experiences implies that men and women suffer similarly and react according to their shared beliefs. This essay explores the prison memoirs of four Latin American women. Each account uses a standardized prison narrative adjusted to suit the narrator's own purpose and hints at how sexuality and motherhood, which shape women's experiences in prison, have been removed from sight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The present study employed qualitative content analysis to examine published personal accounts of currently and formerly incarcerated women in order to deepen our understanding of their experiences in the criminal justice system. Content analysis has been used previously to examine issues related to women and criminal justice, including sexual assault during incarceration (Alarid, 2000), risk and resilience factors among incarcerated mothers (Schlager & Moore, 2014), gender differences in the experience of military imprisonment (Treacy, 1996), and civilian interest in criminal proceedings for entertainment purposes (Dirks, Heldman, & Zack, 2015). However, no empirical studies were found which examined women's experiences of incarceration while also emphasizing the implications for social work practice and criminal justice reform.…”
Section: Methodsmentioning
confidence: 99%
“…The present study employed qualitative content analysis to examine published personal accounts of currently and formerly incarcerated women in order to deepen our understanding of their experiences in the criminal justice system. Content analysis has been used previously to examine issues related to women and criminal justice, including sexual assault during incarceration (Alarid, 2000), risk and resilience factors among incarcerated mothers (Schlager & Moore, 2014), gender differences in the experience of military imprisonment (Treacy, 1996), and civilian interest in criminal proceedings for entertainment purposes (Dirks, Heldman, & Zack, 2015). However, no empirical studies were found which examined women's experiences of incarceration while also emphasizing the implications for social work practice and criminal justice reform.…”
Section: Methodsmentioning
confidence: 99%
“…Especially in a Latin American prison context gender based violence should be taken into account as a risk factor for mental health deterioration (World Health Organization, 2000). Sexual violence and traumatization are a problem for most women that are imprisoned in a Latin American country (Treacy, 1996). In our sample one women shared her trauma of sexual violence, it is very likely that others preferred not to share their experience.…”
Section: Interpretation and Comparison With The Literaturementioning
confidence: 92%
“…In her research on the prison memoirs of ciswomen 10 incarcerated in the dungeons of various Latin American military dictatorships during the 1970s and 1980s, Mary Jane Treacy comes to the conclusion that interrogations of prisoners were not primarily about gathering facts, because ‘many prisoners had little or no knowledge to give prison authorities’. Drawing on Frank Graziano, Treacy (1996: 132) argues that the questioning and accompanying physical assault formed the core of a ‘ritual enactment of power’ where ‘the prison interrogation room and its torture table became “stages” where the prisoner, having lost control over her body, now lost control over her voice’: It was then not what the victims being interrogated said that motivated the continuation of torture, but rather that they were being made to use their speech against themselves, that their voices were being appropriated and translated into the power that destroyed them…. Whatever was said, the regime was speaking.…”
Section: Erotics Of Racism and The Biopolitics Of Torturementioning
confidence: 99%
“…The victim could only announce their absorption into a monologue that edified the State. (Graziano cited in Treacy, 1996: 132)…”
Section: Erotics Of Racism and The Biopolitics Of Torturementioning
confidence: 99%